Variabel-Variabel Yang Mempengaruhi Tingkat Bagi Hasil Tabungan Mudharabah Pada Industri Perbankan Syariah di Indonesia Periode 2011-2014 - Lauda Huruniang; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this research is examine the influence of non performing financing (NPF), financing to deposit ratio (FDR), total revenue, and BI rate toward trustee profit sharing mudharabah Islamic Bank Industries in Indonesia start from January 2011 until June 2014 periods. This research uses quantitative approach. The analysis method used in this research is the method of multiple linear regression analysis of time series with a significance level of 0,05.The result showed that performing financing (NPF) and BI rate have significant influence toward trustee profit sharing mudharabah partially, while financing to deposit ratio (FDR) and total revenue does not influence trustee profit sharing mudharabah significantly. However, non performing financing (NPF), financing to deposit Ratio (FDR), total revenue, and BI rate have significant influence toward trustee profit sharing mudharabah simultaneously.